Stakeholders’ engagement in sustainability development and reporting: Evidence from Brazil - Imoniana, Joshua Onome; Domingos, Luis Carlos; Soares, Renato Ribeiro; Tinoco, João Eduardo Prudêncio (Anais do Congresso Brasileiro de Custos - ABC)
The aim of this study was to compare and contrast the parameters of sustainability development and reporting; and the degree of stakeholders’ engagement in the processes of social control of the Municipalities of Santo Andre, São Bernardo do Campo, São Caetano do Sul, and Diadema (ABCD) of the greater São Paulo, Brazil. This seems to have been ignited by social responsibilities reporting stimulated by the Multi-National Companies (MNC) to abridge the information gap between the companies and stakeholders. With increasing attention to sustainable business, reporting by MNCs about the social and environmental dimensions of their activities – alongside their economic impacts – has become rather common. The transparency of fiscal management in Brazil, from the Fiscal Responsibility Act has become a legal requirement that can be regularly monitored and supervised by stakeholders. However, a transparent public management goes beyond the disclosure of the instruments of fiscal transparency, but extends to the implementation of the concept of accountability, by enabling citizens to monitor and effectively participate in the acts of government that impact across society. As it is indisputable that stakeholder is a centerpiece of the reporting process worldwide, the engagement of these stakeholders become very relevant. The municipalities of ABCD region selected for examination are very relevant to the Brazilian society (context) in that they count as models for social development, emulated by other municipalities of the country. Our research inquires: what characterizes how, why, by whom and to which directions sustainability reporting is nurtured in Brazilian municipalities? In order to provide for the aforementioned, we adopted a descriptive analysis of multi-case studies for the models of participation of the stakeholders in the sustainable enforcement. We performed content analysis on source documents provided by the said municipalities in their corporate web pages in their processes of sustainability reporting based on the realities of the four environments considering the criteria proposed by Global Reporting Initiative. Overall, our analysis of the data makes us to infer that in order to understand the sustainability reporting in the Brazilian public agencies one ought to know the cornerstone of accountability and transparency which is the fiscal responsibility act. Thus, we built up the concept of “sustainability reporting” which could support researchers and practitioners to interpret the contextual background for understanding reporting in an emerging economy. This in turn paves way for further studies such as comparing the sustainability development and reporting of the municipality in emerging countries with that of the developed economy.